OVERCOMING THE TYRANNY OF LOW EXPECTATIONS, DIAGNOSIS, AND VICTIMHOOD - Jackson, Fay (Cadernos Brasileiros de Saúde Mental/Brazilian Journal of Mental Health, 2021)
My mental health issues began with childhood sexual abuse and the physical and emotional ramifications of this. My teen and adult years were mapped by periods of suicidality, depression, anxiety and self-medication with alcohol and marijuana. Distressing voices and images plagued my waking hours and regular sleep evaded me. I was diagnosed with Bipolar Schizoaffective Disorder and informed by a psychiatrist: “You will never work and never be a valuable member of society”. This prognosis and diagnosis caused a worsening of depression and shame. However, I accepted it as fact and saw myself as a victim of my abusers, my diagnosis, enforced treatment and my prognosis.A psychiatric diagnosis coupled with victimhood and the tyranny of low expectations often marginalises and alienates people from society and from reaching their full potential. At the age of 40, a peer worker compassionately challenged me to shake off the imposed low expectations of psychiatrists, family, community and myself. Although I had never previously held permanent employment, within a short time, I became a peer worker. Over the course of my lived experience career, I have held executive positions including being the Director of Consumer and Carer Affairs in a public mental health service, Deputy Commissioner with a state Mental Health Commission, founder of a training and consultancy business and General Manager of Inclusion for a large mental health community managed organisation. People with lived experience deserve to meet their full potential and be contributing members of society and their families.